ANALYSIS OF THE EFFECT OF ACCOUNTING UNDERSTANDING, ACCOUNTING INFORMATION SYSTEMS, AND ORGANIZATIONAL CULTURE ON THE QUALITY OF MSME FINANCIAL REPORTS - Florencia Irena Lawita; Rousilita Suhendah (Jurnal Apresiasi Ekonomi, 2026)
This study aims to examine the influence of accounting knowledge, accounting information systems, and organizational culture on the quality of financial statements in Micro, Small, and Medium Enterprises (MSMEs). The background of this study is based on the importance of quality financial statements as a basis for decision making and a form of accountability in MSME financial management. The research method used is a quantitative approach with data collection through the distribution of questionnaires to MSME actors in Indonesia. The collected data was then analyzed using multiple linear regression techniques to see the relationship and influence between variables. The results show that accounting knowledge has a significant effect on financial statements. Similarly, accounting information systems have a significant influence on improving the quality of financial statements. In addition, organizational culture also has a significant impact on the quality of MSME financial statements. These findings emphasize the importance of improving the competence of MSME actors in the field of accounting, implementing appropriate accounting systems, and establishing an organizational culture that upholds integrity and accountability. Further research is recommended to add other relevant variables and use mixed methods for more comprehensive results.